EFFECT OF DIFFERENT MODELS OF RING SPINNING FRAMES UPON TENSILE PARAMETERS OF 23'S POLYESTER! COTTON BLENDED YARN: ??Short Communication (Biological Sciences - PJSIR, 1999)
The statistical analysis of variance for single yarn strength,elongation and rupture per kilometer presented in Table 2indicates that the effect of different models of ring frames onthese parameters is highly significant. The comparison ofindividual mean values for tensile parameters by DuncanMultiple Range (DMR) test is presented in Table 3.It is clear from the results that the quality of yarn is significantlyeffected by different makes and models of ring framesand newer models of ring spinning machines definitely producedsuperior quality yarn. The finding are in agreement withthat of Douglas (1989) and it may be concluded that the quality